Development of A Structural Equation Model of The Variables Affecting the Organizational Performance of The Mass Rapid Transit Systems of Thailand - Sutep Punthupeng; Thepparat Phimolsathien (Revista de Gestão Social e Ambiental, 2024)
Introduction: The development of the Thai transport system in the future must be based on the advancement of three aspects: personnel, technology, and research and development must be promoted for the operation of efficient innovative tools and management as key mechanisms in the transport system’s development. The master plan of the Ministry of Transport under Strategy 5 for the development of the Thai transport system within 20 years (2017-2036) stated about the need for and initiation of technology and innovation, as well as the promotion of research and development for the application of rapid advancements within these aspects so to develop the transport infrastructure and management, which would engender higher efficiency of future transport as well. Technology is required and is suitable for the analysis and evaluation of performance in the view of safety technological innovation for subway station construction. Objective: The main objective was to explore the development, congruence, and the indirect direct, and total effects of the variables affecting the organizational performance of the mass rapid transit systems of Thailand Method: This is quantitative research, collecting data from 385 executives and chiefs of organizations relating to the mass railway transit systems and private manufacturers participating in the project with state enterprise agencies. Result: Relationship between the two variables and among the multiple variables in conjunction with the estimation of the effects of the variables, which were obtained from the regression coefficients (coef.) of each individual relationship path following the hypothesis. The results indicated that all C.R. ( t-test) values were statistically significant ( > 1.96). Thus, every hypothesis was supported. Technology directly affects organizational performance (coef. = 0.143, p < 0.05). Technology directly affects innovation (coef. = 0.370, p < 0.001). Technology directly affects research and development (coef. = 0.786, p < 0.001). Research and development directly affects innovation (coef. = 0.624, p < 0.001). Research and development directly affects organizational performance (coef. = 0.449, p < 0.001). Innovation directly affects organizational performance (coef. = 0.372, p < 0.01). Conclusion: Technology, innovation, and research and development truly affect organizational performance. The industrial sector should be more encouraged to participate in technology learning and to step into the manufacturing chain for the development of Thailand’s rail transport system. This would also save foreign currency, create employment opportunities in the country, and have continual economic effects for the national monetary circulation, which would eventually pave the way to the enhancement as well as development of the people’s abilities in the future.
Keywords: Quality and Supply Management; Urban Transport Systems Analysis; Maritime Ports and Logistics